RPGRorf15 nanopore long-read sequencing improves retinitis pigmentosa molecular diagnosis for men and women - Manon Fabard; Aurore Devos; Anaïs F. Poncet; Jean-Pascal Meneboo; Martin Figeac; Céline Villenet; Isabelle Drumare; Sabine Defoort-Dhellemmes; Isabelle Meunier; Xavier Zanlonghi; Olivier Grunewald; Vincent Huin; et al. (Human Genetics, 2026)
RPGR (Retinitis Pigmentosa GTPase Regulator ) is the main gene involved in X-linked retinitis pigmentosa (RP) and up to 28% of sporadic RP. Pathogenic variants are mostly located in its retina-specific transcript, RPGRorf15 , especially in the terminal exon named open reading frame 15 (ORF15) , which is a highly repeated region. Because of this complex sequence, first- and second-generation short-read sequencing are difficult, both for male patients and for affected and relative females, resulting in numerous unresolved cases. Long-read sequencing appears to be the most appropriate to counter this problem. Using Oxford Nanopore Technology sequencing, we analysed 194 patients with retinal dystrophy (RD) (142 men and 52 women) suspected to be either X-linked ( n = 42) or autosomal ( n = 152), and for whom first-line sequencing of 230 retinal dystrophy genes, including RP2 and RPGRex1-19 , was negative. Pathogenic ORF15 variants were found in 27 patients (13.9%), 21 men and 6 women. Of the 42 XLRD patients, 15 were carriers (35.7%), nine men and six women, most of them had rod-cone dystrophy. Of the 152 patients with isolated RD, only 12 carried ORF15 variants (7.9%),all male patients, most of them had cone-rod dystrophy (41.7%). We demonstrate the efficacy of this technology to diagnose male cases with a family history of X-linked RD, as well as sporadic cases clinically not suggestive of ORF15 . We also show how easy it is to analyse female carriers or affected women. We expect that more heterozygous women with severe disease and no family history will be identified by this technique in the future.